Exploring experiences of counselors in crisis intervention of natural disasters in Malaysia - Zakaria, Mohd. Zaliridzal (2018)
Crises such as natural disaster are an intrinsic part of life and despite efforts aimed at prevention, crises will continue to occur. Apart from the disaster survivors related issues, counselors are also vulnerable on becoming affected physically and psychologically due to providing assistant for people who are affected by the natural disaster. The main objective of this qualitative research was to conduct a descriptive phenomenological study to explore, understand, and describe the experience of providing crisis interventions during natural disaster among Malaysian counselors. The researcher was the primary instrument for data collection and analysis. Data included field notes and individual semi-structured in-depth interviews. The researcher developed coding categories using ATLAS.ti 7th version. Themes emerged, were refined, and became the six master themes for this research: the immediate response, the disaster survivors, the disaster responders, post-disaster, psychological preparation, and holistic support. This research found that the experiences gained by the counselors are not only within themselves as disaster responders but also with the disaster survivors surrounding them during the disaster situations. The experiences shared by the counselors have also portrayed from the perspectives during the immediate response together with descriptions on the post-disaster support during crisis interventions of natural disaster. Research findings implications, implications for policy and implications for counselors’ practices in Malaysia, as well as future research opportunities are thoroughly discussed in this research. From this research, it was informed that providing crisis intervention and psychological support during natural disaster has brought plethora of experience and knowledge that should be shared by counselors not only with their colleagues but also with other disaster responders in Malaysia.